2007
DOI: 10.2527/jas.2006-715
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of phosphorus balance data from growing pigs

Abstract: Many studies have highlighted concerns over current methods of determining endogenous P losses and P requirements in growing pigs. Therefore, a database containing observations on 350 pigs was assembled from various studies. Four functions for analyzing P balance data were considered: 1) a straight line, 2) a diminishing returns function (monomolecular), 3) a sigmoidal function with a fixed point of inflection (Gompertz), and 4) a sigmoidal function with a flexible point of inflection (Richards). The nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 20 publications
6
26
1
Order By: Relevance
“…In support of the monomolecular model that predicts N excretion better, Kebreab et al (35) noted that the monomolecular equation was best at determining efficiencies of phosphorus utilisation for body weight gain compared with the sigmoidal model. Schulin-Zeuthen et al (23) also showed that the monomolecular model was the best predictor of the relationship between phosphorus retention and available phosphorus intake compared with linear and Gompertz models. In their study (23) , the Gompertz model was better than the linear one as observed for the relationship between UN excretion and NI in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In support of the monomolecular model that predicts N excretion better, Kebreab et al (35) noted that the monomolecular equation was best at determining efficiencies of phosphorus utilisation for body weight gain compared with the sigmoidal model. Schulin-Zeuthen et al (23) also showed that the monomolecular model was the best predictor of the relationship between phosphorus retention and available phosphorus intake compared with linear and Gompertz models. In their study (23) , the Gompertz model was better than the linear one as observed for the relationship between UN excretion and NI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These were a relationship exhibiting diminishing returns behaviour (monomolecular) and a relationship exhibiting sigmoidal behaviour (Gompertz) (22) . The PROC NLMIXED of SAS was used to parameterise the monomolecular and Gompertz functions with a little modification of the equation used by Schulin-Zeuthen et al (23) and the exponential model in the following forms:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations